Bacterial isolates, antimicrobial susceptibility and multidrug resistance in cultures from samples collected from beef and pre-production dairy cattle in New Zealand (2003–2016). Issue 4 (4th July 2019) - Lawrence, KE; Wakeford, L; Toombs-Ruane, LJ; MacLachlan, C; Pfeffer, H; Gibson, IR; Benschop, J; Riley, CB
ABSTRACT: Aims: To describe the common species and the antimicrobial susceptibility of bacteria cultured from samples submitted to commercial veterinary diagnostic laboratories from beef and pre-production dairy cattle between 2003–2016, and to describe the proportion of isolates with multidrug resistance (MDR). Methods: Bacterial culture and antimicrobial susceptibility data from July 2003 to March 2016 were obtained from commercial veterinary diagnostic laboratories in New Zealand. Results were included from samples from beef cattle, irrespective of age or sex, dairy-breed females aged <2 years and dairy-breed males of any age. Submission information provided included the specimen description, the organisms cultured, and the antimicrobial susceptibilities of isolates, if tested. Antimicrobial resistance (AMR) was defined as any isolate not showing susceptibility to an antimicrobial compound and MDR as any isolate showing AMR to ≥3 antimicrobial classes. Results: There were 1, 858 unique laboratory submissions, yielding 2, 739 isolates. Of these submissions, most were from the Canterbury (389; 21.9%), Manawatu (388; 21.9%) Waikato (231; 12.4%) and Hawke's Bay (136; 7.3%) regions. There were 163 unique species identifications for the 2, 739 isolates; the most common were Yersinia pseudotuberculosis (452; 16.5%), Campylobacter jejuni (249; 9.1%), E s cherichia coli (230; 8.4%) and Salmonella enterica serovar Typhimurium (143; 5.2%). Only 251/2, 739 (9.2%) isolates from 122/1, 858 (6.6%) submissions had antimicrobial susceptibility results. There were no sensitivity results for Yersinia spp., and only one each for Salmonella spp., and Campylobacter spp. Amongst the isolates tested, susceptibility to ampicillin was lowest (33/56; 58.9%). Overall, 57/251 (20.7%) isolates tested for antimicrobial susceptibility had MDR, and MDR was most common for Enterococcus spp. (12/17; 71%) and E. coli (13/30; 43%). Conclusions and Clinical Relevance: This is the first report on antimicrobial susceptibility and MDR in New Zealand beef and pre-production dairy cattle. Findings highlight the limited use of bacterial culture and sensitivity testing by veterinarians and deficits in the information accompanying submissions. A national antimicrobial resistance surveillance strategy that specifically includes this population is recommended.